Rapid and reversible reactions of [NiFe]-hydrogenases with sulfide. - Vincent, K; Belsey, N; Lubitz, W; Armstrong, F (2006)
Rapid and reversible binding of sulfide to [NiFe]-hydrogenases (particularly the enzyme from Desulfovibrio vulgaris) under weakly acidic conditions (pH 6) has been studied by protein film voltammetry, which tracks the formation of different species as a function of potential. Sulfide (most likely entering as H2S) rapidly attacks the active site during H2 oxidation. The inactive adduct is formed (and is stable) only at potentials substantially more positive than the comparable species formed with oxygen species and is easily reactivated upon reduction. The sulfide adduct also reacts further with O2 to produce a new species that undergoes reductive activation very slowly. The results clarify complex and controversial chemistry reported in the literature and provide insight into how these enzymes would cope with sulfide production in sulfate-reducing bacteria.